Viral Outbreak in Corals Associated with an In Situ Bleaching Event: Atypical Herpes-Like Viruses and a New Megavirus Infecting Symbiodinium - Correa, Adrienne M. S.; Ainsworth, Tracy D.; Rosales, Stephanie M.; Thurber, Andrew R.; Butler, Christopher R.; Vega Thurber, Rebecca L. (Frontiers in Microbiology, 2016)
Previous studies of coral viruses have employed either microscopy or metagenomics, but few have attempted to comprehensively link the presence of a virus-like particle (VLP) to a genomic sequence. We conducted transmission electron microscopy imaging and virome analysis in tandem to characterize the most conspicuous viral types found within the dominant Pacific reef-building coral genus Acropora. Collections for this study inadvertently captured what we interpret as a natural outbreak of viral infection driven by aerial exposure of the reef flat coincident with heavy rainfall and concomitant mass bleaching. All experimental corals in this study had high titers of viral particles. Three of the dominant VLPs identified were observed in all tissue layers and budding out from the epidermis, including viruses that were ~70 nm, ~120 nm, and ~150 nm in diameter; these VLPs all contained electron dense cores. These morphological traits are reminiscent of retroviruses, herpesviruses, and nucleocytoplasmic large DNA viruses (NCLDVs), respectively. Some 300-500 nm megavirus-like VLPs also were observed within and associated with dinoflagellate algal endosymbiont (Symbiodinium) cells. Abundant sequence similarities to a gammaretrovirus, herpesviruses, and members of the NCLDVs, based on a virome generated from five Acropora aspera colonies, corroborated these morphology-based identifications. Additionally sequence similarities to two diagnostic genes, a MutS and (based on re-annotation of sequences from another study) a DNA polymerase B gene, most closely resembled Pyramimonas orientalis virus, demonstrating the association of a cosmopolitan megavirus with Symbiodinium. We also identified several other viral particles in host tissues, along with sequences phylogenetically similar to circoviruses, phages, and filamentous viruses. This study suggests that viral outbreaks may be a common but previously undocumented component of natural bleaching events, particularly following repeated episodes of multiple environmental stressors.